Identification of important mechanical and acoustic parameters for the sensory quality of cocoa butter alternatives. (October 2015) - Gregersen, S.B.; Povey, M.J.W.; Kidmose, U.; Andersen, M.D.; Hammershøj, M.; Wiking, L.
Abstract: In this study, the correlation between sensory attributes and the mechanical and acoustic properties of cocoa butter alternatives was elucidated. Needle penetration, cone penetration and compression tests were used to characterise mechanical properties and acoustic properties were evaluated by simultaneous texture and sound analyses. Results were correlated with a descriptive sensory evaluation. A significant correlation was found between hardness (needle penetration) and sensory hardness evaluated upon biting ( r = 0.91, p < 0.05) and between Hencky strain (compression test) and the sensory toughness ( r = 0.94, p < 0.05). In contrast, no significant correlation was found between brittleness (cone penetration) and the sensory brittleness. The use of different mechanical methods shed light on a complex rheological behaviour of fat which demonstrates the importance of not simply relying on results from penetration tests when evaluating fat texture. For instance, a hard fat was perceived very differently depending on the degree of elasticity. A significant correlation was found between sound pressure level (simultaneous sound and texture analyses) and the sensory evaluation of the sound intensity upon breakage ( r = 0.96 and 0.97, p < 0.05). Both hardness and elasticity were found to be of great importance for the intensity of the sound emission i.e. a hard texture with a low degree of flexibility (less elastic) is more likely to provide a rapid energy release upon breakage and thus a high intensity sound emission. Highlights: In this study fats used in the chocolate and confectionery industry were evaluated. Mechanical and acoustic properties were correlated with sensory attributes. Force from needle penetration test was highly correlated with sensory hardness. Hencky strain from compression test was highly correlated with toughness. Instrumental and sensory evaluation of sound were found to be highly correlated.